Severe Paroxysmal Sinus Bradycardia Associated With High-Frequency Oscillatory Ventilation - Mellema, James D.; Baden, Harris P.; Martin, Lynn D.; Bratton, Susan L. (Chest, 1997)
To determine the incidence of and risk factors for unexplained paroxysmal bradycardia in children treated with high-frequency oscillatory ventilation (HFOV). A nested case-control study. A university-affiliated children's hospital. All children treated with HFOV for at least 3 days during a 2-year period and a randomly chosen comparison group of 50 children treated with only conventional mechanical ventilation (CMV) for at least 3 days during the same time period. None. Unexplained paroxysmal sinus bradycardia occurred in six children (12%) receiving HFOV, and was significantly more common than in children treated with CMV (0%). The bradycardic events occurred after the lung disease started to improve, and the mean airway pressure (mPaw) at the time of the bradycardias was significantly decreased from the child's maximal mPaw. The bradycardic events were effectively treated acutely with manual ventilation or atropine sulfate, and resolved completely after the patient was changed to a regimen of CMV. Unexplained paroxysmal bradycardia associated with HFOV in children is not uncommon. It completely resolves with conversion to CMV and may be related to overdistention of alveoli as compliance improves.